Exploring the Experience of Breast Cancer for Women of Different Age Groups: A Critical Review - Dupeyron, Sarah (2014)
Abstract Aim To compare and contrast the experience of breast cancer in women of different biopsychosocial stages of their life Background Breast cancer is the most common cancer in women in the UK and worldwide. The experience of breast cancer is dynamic and complex and is comprised of many challenges and opportunities for growth. To achieve high quality, holistic care, the needs and concerns of breast cancer patients need to be understood by healthcare professionals. Method A critical review method was chosen and a range of databases were used to provide a variance of sources and literature types Findings Issues that affect all ages of women with breast cancer include aging-related problems, psychological matters, support, family, roles and body image, sexuality and femininity. Young women also have fertility related issues and older women have specific comorbidity issues. These all affect the self, situation, support and strategies that are needed to adjust to life transitions, such as breast cancer. Women also use an internalised clock to assess whether their lives are on time, and breast cancer affects life plans, which causes psychological distress. Conclusion To achieve holistic care, healthcare professionals need to carry out thorough assessment of women’s needs and concerns during breast cancer. The experience varies with age, is complex and diverse and goes beyond the breast itself. This review highlights the importance of holistic care and what illness means to patients on an individual level.